2010
DOI: 10.1080/09297041003601470
|View full text |Cite
|
Sign up to set email alerts
|

Event-Based Prospective Memory in Children with Sickle Cell Disease: Effect of Cue Distinctiveness

Abstract: Event-based prospective memory (EB-PM) is the formation of an intention and remembering to perform it in response to a specific event. Currently, EB-PM performance in children with sickle cell disease (SCD) is unknown. In this study, we designed a computer-based task of EB-PM; No-Stroke, Silent-Infarct, and Overt-Stroke groups performed significantly below the demographically similar control group without SCD. Cue distinctiveness was varied to determine if EB-PM could be improved. All groups, with the exceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 71 publications
1
10
0
4
Order By: Relevance
“…Regarding the effects of demographic variables on EB-PM performance, no gender effect was found, which is consistent with studies of normal adults (Einstein and McDaniel, 1990;Kidder et al, 1997;Maujean et al, 2003), typically developing children (Kerns, 2000;Kerns and Price, 2001), children with TBI (McCauley et al, 2009, 2010a, and children with sickle cell disease (McCauley and Pedroza, 2010). Although socioeconomic status (SES) is a well-known moderator of outcome in children with TBI (Taylor, 2004;Taylor et al, 1999Taylor et al, , 2002Yeates et al, 1997), no significant effect of SES on EB-PM performance was found.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Regarding the effects of demographic variables on EB-PM performance, no gender effect was found, which is consistent with studies of normal adults (Einstein and McDaniel, 1990;Kidder et al, 1997;Maujean et al, 2003), typically developing children (Kerns, 2000;Kerns and Price, 2001), children with TBI (McCauley et al, 2009, 2010a, and children with sickle cell disease (McCauley and Pedroza, 2010). Although socioeconomic status (SES) is a well-known moderator of outcome in children with TBI (Taylor, 2004;Taylor et al, 1999Taylor et al, , 2002Yeates et al, 1997), no significant effect of SES on EB-PM performance was found.…”
Section: Discussionsupporting
confidence: 82%
“…This was unfortunate as it could have demonstrated the degree to which impaired retrospective memory abilities may have accounted for impaired EB-PM performance in these children. Studies have found that PM and retrospective memory are clearly dissociable (Maylor et al, 2002;Palmer and McDonald, 2000;West and Craik, 2001;West and Krompinger, 2005) and are not strongly related in adults and healthy elderly (Brandimonte and Passolunghi, 1994;Driscoll et al, 2005;Einstein and McDaniel, 1990;Huppert and Beardsall, 1993;Kidder et al, 1997;Kvavilashvili, 1987;Maylor, 1990;McDaniel and Einstein, 1993; Salthouse et al, 2004), typically developing children (Kvavilashvili et al, 2001), children with chronic TBI (McCauley et al, 2009), or children with sickle cell disease (McCauley and Pedroza, 2010). The close relation of these two memory categories has been demonstrated in early development, but they reportedly diverge very rapidly thereafter (Guajardo and Best, 2000;Ruther and Best, 1993).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although far less studied, no significant gender effect on PM has been reported in typically-developing children either (Kerns, 2000; Kerns & Price, 2001). Previous work in children with subacute (McCauley, et al, 2010) and chronic (McCauley, et al, 2009) TBI have failed to find a significant effect of gender, and a recent study of EB-PM in children with sickle cell disease has also failed to find a gender effect (McCauley & Pedroza, 2010). Although SES has been shown to moderate outcomes of children with TBI (Taylor, 2004; Taylor et al, 1999; Taylor et al, 2002; Yeates, et al, 1997), no significant effect of SES on EB-PM performance was found in our sample at three months postinjury and this result is similar to findings in pediatric TBI studies by McCauley and colleagues (2009; 2010) and a recent study in children with sickle cell disease (McCauley & Pedroza, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies have reported that PM and RM are not strongly associated in adults and healthy elderly (Brandimonte & Passolunghi, 1994; Driscoll, McDaniel, & Guynn, 2005; G. O. Einstein & M. A. McDaniel, 1990; Huppert & Beardsall, 1993; Kidder, et al, 1997; Kvavilashvili, 1987; Maylor, 1990; McDaniel & Einstein, 1993; Salthouse, Berish, & Siedlech, 2004), typically-developing children (Kvavilashvili, Messer, & Ebdon, 2001), or most recently, children with sickle cell disease (McCauley & Pedroza, 2010). RM and PM appear to be closely related quite early in development, but tend to dissociate rapidly; there is evidence that by the age of five years, these two memory domains are distinct (Guajardo & Best, 2000; Ruther & Best, 1993).…”
Section: Discussionmentioning
confidence: 99%